2019
DOI: 10.1136/archdischild-2018-316750
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of gut oxygenation in the neonatal population using near-infrared spectroscopy: a clinical tool?

Abstract: ContextNear-infrared spectroscopy (NIRS) is a non-invasive bedside monitor of tissue oxygenation that may be a useful clinical tool in monitoring of gut oxygenation in newborn infants.ObjectiveTo systematically review literature to determine whether NIRS is a reliable tool to monitor gut oxygenation on neonatal units.Data sourcesPubMed and Embase databases were searched using the terms ‘neonate’, ‘preterm infants’, ‘NIRS’ and ‘gut oxygenation’ (2001–2018).Study selectionStudies were included if they met inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…With regard to applicability in clinical practice, it is difficult to know how far we can extrapolate findings from physiological studies such as this. Splanchnic NIRS measurements have not been validated in the same way as cerebral NIRS measurements [20] and this fundamentally limits what we can infer clinically from these results. The study was limited by a low background incidence of NEC, with no eligible infant developing NEC during the study period or at any stage during hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to applicability in clinical practice, it is difficult to know how far we can extrapolate findings from physiological studies such as this. Splanchnic NIRS measurements have not been validated in the same way as cerebral NIRS measurements [20] and this fundamentally limits what we can infer clinically from these results. The study was limited by a low background incidence of NEC, with no eligible infant developing NEC during the study period or at any stage during hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…First, our review describes the mechanistic strategies available to neonatal and mature intestine to maintain adequate oxygenation, but does not include the contribution of these strategies during external influences that may alter intestinal oxygen supply or demand, e.g., anemia and enteral feeding. Nevertheless, our speculations on implications of these external influences on intestinal oxygenation are supported by recent reviews in both animal models and preterm neonates (18,19,44). Second, we purposely did not take into account factors that may influence the maturation processes described.…”
Section: Interpretation and Discussionmentioning
confidence: 72%
“…Near-infrared spectroscopy (NIRS) is a non-invasive, bedside technique used to continuously monitor regional oxygen saturation (rSO 2 ) (17). Previous studies have reported promising results for splanchnic rSO 2 (r s SO 2 )monitoring for detecting hemodynamic changes that accompany physiologic and pathophysiologic conditions (18,19). Currently, the use of splanchnic NIRS remains mostly limited to research settings.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Preliminary studies have suggested that NIRS profiles may differ in terms of mean mesenteric r-SO 2 values and variations in the weeks or days preceding the occurrence of NEC. [9][10][11][12] However, these studies and other works using various NIRS-derived tissue oxygenation indexes 13,14 have not considered the potential role of NIRS in the early diagnosis of NEC in a newborn with gastrointestinal signs pointing to this disease, such as feeding intolerance or bloody stools. The objective of this study was to assess the ability of NIRS to diagnose NEC in neonates with bloody stools and/or abdominal distension.…”
mentioning
confidence: 99%